The age of supergene manganese deposits in Katanga and its implications for the Neogene evolution of the African Great Lakes Region - (:unkn) unknown (My University, 2015)
Supergene manganese deposits commonly contain K-rich Mn oxides with tunnel structure, such ascryptomelane, which are suitable for radiometric dating using the 39Ar–40Ar method. In Africa, Mn depositshave been dated by this method for localities in western and southern parts of the continent, whereas onlysome preliminary data are available for Central Africa. Herewe present new39Ar–40Ar ages for Mnoxide samplesof the Kisenge deposit, in southwestern Katanga, Democratic Republic of the Congo. The samples represent supergeneMn oxide deposits that formed at the expense of primary Paleoproterozoic rhodochrosite-dominatedcarbonate ores. Main phases of Mn oxide formation are dated at c. 10.5 Ma, 3.6 Ma and 2.6 Ma for a core thatcrosses a mineralized interval. The latter shows a decrease in age with increasing depth, recording downwardpenetration of a weathering front. Surface samples of the Kisenge deposits also record a ≥c.19.2 Ma phase, aswell as c. 15.7 Ma, 14.2 Ma and 13.6 Ma phases. The obtained ages correspond to distinct periods of paleosurfacedevelopment and stability during the Mio-Pliocene in Katanga. Because Katanga is a key area bordered to theNorth by the Congo Basin and to the East by the East African Rift System, these ages also provide constraintsfor the geodynamic evolution of the entire region. For the Mio-Pliocene, the Kisenge deposits record ages thatare not systematically found elsewhere in Africa, although the 10.5–11 Ma event corresponds to a roughly simultaneousevent in the Kalahari Manganese Field, South Africa. The rest of the Katanga paleosurface record differssomewhat fromrecords for other parts of Africa, forwhich older, Eocene ages have been obtained. This differenceis most probably related to the specific regional geodynamic context: uplift of the East African Plateau, with associatederosion, and the opening of the East African Rift System at c. 25 Ma are events whose effects, in thestudy area, interfere with those of pr
Keywords: African Research